(untitled) (Archives of Mechanics - Test, 2000)
A simple unified procedure is applied to derive irreducible nonpolynomial representations for scalar-, vector-, skewsymmetric and symmetric second order tensor-valued anisotropic constitutive equations involving any finite number of vector variables and second order tensor variables. In this part, our concern is for the crystal classes and quasicrystal classes D2m+1h and D2md for all integers m ≥ 1.